An update on the Clean Development Mechanism in Africa in times of market crisis. (23rd February 2017) - Kreibich, Nicolas; Hermwille, Lukas; Warnecke, Carsten; Arens, Christof
Abstract : Africa and in particular African Least Developed Countries have to a large extent been neglected by the Clean Development Mechanism (CDM). This article reviews the mechanism's performance in the region and highlights current developments. The analysis is based on a quantitative breakdown of data provided by the United Nations Environment Programme and Technical University of Denmark (UNEP/DTU) CDM Pipeline and was complemented by interviews with selected investors. The findings indicate that despite the various support measures for underrepresented regions, the overall share of African CDM activities continues to be low. The significant rise in the share of Programmes of Activities of recent years cannot make up for the continuing low numbers of African stand-alone projects. Further, the collapse of the compliance market has proved fatal in terms of timing: ongoing efforts to support the development of a genuine African carbon market were suffocated by the lack of demand for Certified Emission Reductions at a moment when capacity building had started to bear fruit. Consequently, instead of being a mitigation tool with significant scale, the future role of the CDM in Africa might be limited to the voluntary market, while at the same time serving as a tool to foster sustainable development, with mitigation benefits.